(untitled) (Sustainability in Debate, 2011)
Climate change, rising oil prices and the global financial crisis has put sustainability and ‘green growth’ of the economy on the political agenda. While the transition towards a “low carbon” economy in developed countries like in the European Union should mainly be found in renewable energy production, developing countries like Brazil face with high land use emissions which will further rise in the coming decades without proper policy instruments. Deforestation and cattle production are the main sources of land use emissions in Brazil and we expect that these emissions will further rise with liberalisation of agricultural trade. A transition towards a “low carbon” economy in Brazil thus calls for appropriate, and effective land-use policies. Agricultural intensification on one hand can meet the world demand for soy and beef. For example we calculate that increasing the meat content of cattle can reduce emissions from deforestation up to 30%, but intensification may also accelerate further deforestation of Cerrado and Amazon forests. In order to avoid such additional deforestation, large areas of degraded lands have to be taken back into production, which requires large agricultural investments. In addition, (new) economic instruments, monitoring, law enforcement and appropriate conservation policies are also needed to halt further deforestation and biodiversity loss. The recently amended change of the Forest Code policy, for example, is expected to accelerate deforestation further, thus making more difficult to reach mitigation targets for the Brazilian State.